SURVEY PUBLIC FINANCE MANAGEMENT (PFM) DI KABUPATEN FLORES TIMUR PROVINSI NUSA TENGGARA TIMUR - Thomas Ola Langoday (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2011)
This study aims to see how far the implementation of the performance of PublicFinancial Management (PFM) in accordance with applicable standards and regula-tions. The survey shows that in general the performance of public financial manage-ment in East Flores Regency categorized as very good; from the nine areas that wereanalyzed, seven areas were very good in the category of regulatory framework; Plan-ning and Budgeting: Cash Management: Procurement of Goods and Services; Debtand Public Investment: Asset Management, and the last External Audit and Over-sight. One area is in both categories of Internal Control and the fields are at very lowcategory of Accounting and Reporting. The result of this study recommends that theforce placed on each SKPD or Bachelors degree in Accounting and Finance for fi-nancial management in a professional area. In the extreme, this study recommendsthat the chief of Budget, Accounting, Accounting and Reporting, and Verification atthe Department of Finance and Asset Areas on each District/City should be headed bya person with qualifications or Bachelors degree in Accounting and Finance.Keywords: performance, public financial management, degree in accounting.